Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1038/nature06729
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Roquin represses autoimmunity by limiting inducible T-cell co-stimulator messenger RNA

Abstract: Nature 451, 437-440 (2008) In Fig. 3a, the descriptions of the continuous and dotted curves were inadvertently swapped. The continuous line corresponds to the modified synthetic thermal profile (storms reaching the 60 mbar level). The dotted line corresponds to the Cassini CIRS thermal profile (storms reaching the 160 mbar level). The experiment measures the differential laser transmission through the quantum dot between the on-and off-exciton resonance condition. As a result, the origin in Fig. 2a-h corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 1 publication
1
65
2
Order By: Relevance
“…ICOS has been considered an inducible T-cell costimulatory molecule important for CD40-mediated Ab class switching [30]; however, the recent studies of uncontrolled expression of ICOS in several gene-modified mice showing lupus-like pathology provide insight for the close relationship between ICOS-expressing CD4 1 T cells and autoimmunity [19,31]. In the present study, blockade of ICOS using neutralizing Ab significantly reduced the production of total IgG in RASV-administered MyD88 À/À mice, suggesting possible cross-talk between Tfh-like cells and B cells via ICOS-ICOSL interaction for hyper-IgG.…”
Section: Discussionmentioning
confidence: 99%
“…ICOS has been considered an inducible T-cell costimulatory molecule important for CD40-mediated Ab class switching [30]; however, the recent studies of uncontrolled expression of ICOS in several gene-modified mice showing lupus-like pathology provide insight for the close relationship between ICOS-expressing CD4 1 T cells and autoimmunity [19,31]. In the present study, blockade of ICOS using neutralizing Ab significantly reduced the production of total IgG in RASV-administered MyD88 À/À mice, suggesting possible cross-talk between Tfh-like cells and B cells via ICOS-ICOSL interaction for hyper-IgG.…”
Section: Discussionmentioning
confidence: 99%
“…OX40, 4-1BB, and ICOS have been implicated in the pathogenesis of lupus. [42][43][44] OX40 and 4-1BB magnify the T-cell response through induction of the proliferation of conventional T cells and inhibition of T reg cell-mediated immune suppression. 37,45 The ICOS-mediated signal is essential for the induction of follicular helper T cells, thus it functions as an enhancer of B-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed that roquin represses autoimmunity by limiting ICOS mRNA expression through a microRNA-independent posttranslational repression. 33,34 In addition, a recent study showed that the loss of roquin induced early death and immune dysregulation but not autoimmunity in sanroque mice. 35 Therefore, future studies are required to completely elucidate the mechanisms behind pathogenesis of lupus in sanroque mice.…”
Section: T Fh Cells In Murine Models Of Autoimmune Diseasesmentioning
confidence: 99%